Breaking Bad and Dignity Unity and Fragmentation in the Serial Television Drama - Logan, Elliott; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
An ambitious interpretation of the critically celebrated and widely popular crime drama Breaking Bad , this book argues that not only should the series be understood as a show that revolves around the dramatic stakes of dignity, but that to do so reveals - in new ways - central aspects of serial television drama as an art form.
Keywords: Motion pictures and television; Communication; Arts; Media Studies; Media Research